2015
DOI: 10.1242/jcs.165019
|View full text |Cite
|
Sign up to set email alerts
|

Cells on film – the past and future of cinemicroscopy

Abstract: Movie making is now a ubiquitous experimental tool that biologists use alongside more traditional techniques such as molecular biology and biochemistry. It is no longer just cell biologists, but scientists from many other disciplines, such as immunology and neuroscience, that utilise movies to dissect their processes of interest. When did filming become such a standard laboratory technique? Who developed the use of the movie as an experimental tool? The Wellcome Library has recently restored and digitized a nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The origins of time-lapse microscopy can be traced back to Etienne-Jules Marey, 15,16 who assembled the first documented time-lapse microscope in 1891 and filmed red blood cells. 15,17 In 1895, the Lumiére brothers patented the cinematograph, a device capable of "manipulating" time by speeding up or slowing down recordings during playback. 18 Shortly thereafter, cinematographers started to look at microscopic specimens.…”
Section: Early Time-lapse Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The origins of time-lapse microscopy can be traced back to Etienne-Jules Marey, 15,16 who assembled the first documented time-lapse microscope in 1891 and filmed red blood cells. 15,17 In 1895, the Lumiére brothers patented the cinematograph, a device capable of "manipulating" time by speeding up or slowing down recordings during playback. 18 Shortly thereafter, cinematographers started to look at microscopic specimens.…”
Section: Early Time-lapse Studiesmentioning
confidence: 99%
“…In 1903, Duncan recorded, in one of the earliest microcinematographic movies of living organisms, the movement of cheese mites. 15 In 1907, Ries filmed sea urchin development, 19 and, in 1909, Comandon demonstrated that disease-causing and nondisease-causing syphilis bacteria could be distinguished based on their motility. 16 After the development of tissue culture in 1907 by Harrison 20 and the first commercial microcinematograph in 1914, 21 microcinematography was adopted by Carrel and Rosenberger to study the movement of fibroblasts and macrophages in culture.…”
Section: Early Time-lapse Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Comandon, just as microscopes had opened up the spatial dimension of investigation, the film camera enhanced the temporal dimension of perception, allowing us to see well-known phenomena in a new way or to discover previously imperceptible processes (Landecker 2005(Landecker , 2006(Landecker , 2009.⁴ Ever since the introduction of time-lapse imaging, the development of methods for acquiring, analysing, and understanding images in order to generate numerical information has been the main technological breakthrough in enhancing the manipulability of time. With the so-called 'computer vision', filming allows the observer not only to see events that are not visible in static images, but also to subsequently deal with time as a measurable variable in experiments (Stramer and Dunn 2015).…”
Section: In Vivo Imaging and The Four-dimensional Conceptualization O...mentioning
confidence: 99%